Fragmente der Frühromantik - Strack, Friedrich; Eicheldinger, Martina (De Gruyter, 2011)
Martina Eicheldinger
Description based upon print version of record
Keywords: Quelle; Kommentar; Geschichte 1795-1804; Romantik; Das Fragmentarische; Literatur; Deutsch; Fragment